Lifestyle factors modified the mediation role of liver fibrosis in the association between occupational physical activity and blood pressure - Zhang, Shangyi; Chen, Zhenlong; Jiang, Xinman; Zhou, Shenglan; Liu, Yanru; Liu, Mingsheng; Dai, Xiayun; Lu, Bifeng; Yi, Guilin; Yin, Wenjun (Frontiers in Public Health, 2024)
Objectives The study aimed to estimate the role of liver fibrosis in the association between occupational physical activity (OPA) and blood pressure (BP), which is modified by lifestyle factors. Methods The questionnaire survey and physical examination were completed among 992 construction workers in Wuhan, China. Associations between OPA or lifestyle factors and liver fibrosis indices and blood pressure were assessed using generalized additive models. The mediation analysis was used to evaluate the role of liver fibrosis in the association between OPA and lifestyle factors and BP. Results Moderate/high OPA group workers had an increased risk of liver fibrosis [odds ratio (OR) = 1.69, 95% confidence intervals (CI): 1.16–2.47, P < 0.05] compared with low OPA group workers. Smoking or drinking alcohol was related to liver fibrosis (aspartate aminotransferase to platelet ratio index: OR = 2.22, 95% CI: 1.07–4.62 or OR = 2.04, 95% CI: 1.00–4.15; P < 0.05). Compared with non-drinkers, drinkers were related to a 2.35-mmHg increase in systolic blood pressure (95% CI: 0.09–4.61), and a 1.60-mmHg increase in diastolic blood pressure (95% CI: 0.08–3.13; P < 0.05). We found a significant pathway, “OPA → liver fibrosis → blood pressure elevation,” and lifestyle factors played a regulatory role in the pathway. Conclusion OPA or lifestyle factors were associated with liver fibrosis indices or BP in construction workers. Furthermore, the association between OPA and BP may be partially mediated by liver fibrosis; lifestyle factors strengthen the relationship between OPA and BP and the mediation role of liver fibrosis in the relationship.